Social representations of puerperas about the normal birth center - Rodrigues, Andreia Silva (2020)
This research aims to know the social representations of puerperal women about the normal birth center. The research was exploratory, qualitative, based on the theory of social representations conceived by Moscovici. In data collection, the technique of free word association (TALP) and semi-structured individual interview were used. It took as a scenario a normal birth center located in salvador-BA-Brazil, with participants as a total of 78 mothers over 18 years old. With the TALP data, a database was built for processing in the Iramuteq software, which generated a tree of similarity of the evocations of the mothers on the CPN. The interviews were transcribed and processed using the same software, which issued the descending hierarchical classification dendogram. Approval by the Research Ethics Committee, No. 447,526. The tree allowed the identification of co-occurrences between words and indication of the connection between the axes: humanized, natural, welcoming, caring, home. Such findings were clarified and ratified with a descending hierarchical classification of the interviews. Upon contacting the puerperal women to learn about the social representations about the normal birth center, as well as the reasons and means used to learn about its existence, it was possible to identify that the birth center offers women and their families a humanized service, and consequently, individualized as well as integrated, which makes this scenario suitable to meet the expectations and desires of women.